Coherent population trapping with controlled interparticle interactions - Schempp, Hanna; Günter, Georg; Hofmann, Christoph S.; Giese, C.; Saliba, S. D.; DePaola, B. D.; Amthor, Thomas; Weidemüller, Matthias; Sevinçli, S.; Pohl, T. (Physical review letters, 2010)
We investigate coherent population trapping in a strongly interacting ultracold Rydberg gas. Despite the strong van der Waals interactions and interparticle correlations, we observe the persistence of a resonance with subnatural linewidth at the single-particle resonance frequency as we tune the interaction strength. This narrow resonance cannot be understood within a mean-field description of the strong Rydberg-Rydberg interactions. Instead, a many-body density matrix approach, accounting for the dynamics of interparticle correlations, is shown to reproduce the observed spectral features.